The Use of Group Investigation Model to Improve Student Learning Outcomes in Science Learning in Elementary Schools - Iman, Rasulun (Journal of Indonesian Primary School, 2024)
This learning model can be developed to be better and can be more useful in biology learning, namely not only in the material of Single Substances and Mixed Substances, but can be applied to other materials that have work activities that can be discussed. The learning outcomes of students taught with the cooperative defense model of the group investigation type increased for each cycle. In the pre-cycle, the average student score was 55.65, increasing in cycle I to 73.48 and then increasing again in cycle II to 86.08. The classical student completion in the pre-cycle was 8.69%, in cycle I it increased to 47.82% and continued to increase in cycle II to 86.95%. Student activity in learning with the cooperative learning model of the group investigation type increased better for each cycle. Teacher activity during learning with the cooperative learning model of the group investigation type increased in each cycle. The average score of teacher activity in cycle I was 3.94 and was in the good category, increasing in cycle II to 4.5 and was in the very good category.